Structure of Meaning (SOM): towards a three-dimensional perspective on translating between Chinese and English - Zhu, Chunshen (1993)
The introductory first chapter begins with a brief survey, of translation in the pre-linguistics period. It holds that comparativeness and comparison should be the foundation of translation studies. The model of Structure of Meaning (SOM) is thus created by incorporating and extending the two three-dimensional models provided by systemic-functional grammar and speech act theory. It consists of three dimensions of linguistic composition, interactional dynamic and aesthetic impact, for the analysis of the SL text, for the creation of the TL text in translation, and for the comparison of the two in translation studies. In linguistic composition, the word-order is observed in terms of Agent)-V(erb)O(bject) sequence and its variations, elaborated by modification in text formation. The functions of linguistic elements are classified as syntactic bearer, information carrier and stylistic marker for analysis. The issue of Unit of Translation is also addressed. Information distribution is analyzed for the interactional dynamic of the SOM in terms of implicit versus explicit presentation of information and how this is dealt with in translating on the basis of thematic structure. Aesthetic impact combines form, function and effect to give a SOM its individuality. This is discussed via the translation of figurative language, and syntactic iconicity and enactment. Attention is also devoted to the relations between Shape, Sound and Sense in translation. The model of SOM, in conclusion, identifies Stance and Style within the conventional meaning of 'style', and proposes the practice of stylistic translating in the creation a TL SOM which matches the SL SOM in the three dimensions.